IMPLEMENTASI TEORI KONEKTIVISME DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DI ERA DIGITAL: SYSTEMATIC LITERATURE REVIEW - Jecsonius Robinson; Supiana Supiana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The advancement of digital technology has changed the way learning takes place in education. Learning processes that were previously more traditional are now shifting toward digital learning environments that are more open, interactive, and connected. This development has made Connectivism increasingly relevant in Christian Religious Education learning in the digital era. This study aims to examine the implementation of connectivism theory in Christian Religious Education through a Systematic Literature Review (SLR) approach. The study employed a qualitative method using the PRISMA 2020 stages, including identification, screening, eligibility, and included studies. Data were collected from Scopus and Google Scholar databases covering publications from 2020–2026 and supported by several theoretical references related to connectivism. The findings show that the implementation of connectivism in Christian Religious Education can be seen through the use of digital media, Learning Management Systems (LMS), social media, and network-based learning that support student participation, learning flexibility, and spiritual reflection. On the other hand, the study also identified several challenges, including low teacher digital literacy, technology use that still focuses mainly on technical functions, and the potential for superficial spiritual learning. This study provides a broader understanding of the implementation of connectivism in Christian Religious Education, particularly in relation to digital pedagogy and spiritual learning in the digital era. The findings are expected to contribute to the development of more adaptive Christian Religious Education learning models that are relevant to current educational changes. ABSTRAK Kemajuan teknologi digital membawa perubahan dalam cara proses belajar berlangsung di dunia pendidikan. Pembelajaran yang sebelumnya cenderung bersifat tradisional mulai berkembang ke arah pembelajaran digital yang lebih terbuka, aktif, dan saling terhubung. Perkembangan ini membuat teori Connectivism semakin relevan digunakan dalam pembelajaran Pendidikan Agama Kristen di era digital. Penelitian ini bertujuan mengkaji penerapan teori connectivism dalam pembelajaran Pendidikan Agama Kristen melalui metode Systematic Literature Review (SLR). Penelitian menggunakan pendekatan kualitatif dengan tahapan PRISMA 2020 yang mencakup identifikasi, penyaringan, kelayakan, dan penentuan artikel yang digunakan dalam kajian. Data diperoleh dari database Scopus dan Google Scholar dengan rentang publikasi tahun 2020–2026 serta didukung beberapa referensi teoritis mengenai connectivism. Hasil kajian menunjukkan bahwa penerapan connectivism dalam Pendidikan Agama Kristen terlihat melalui penggunaan media digital, Learning Management System (LMS), media sosial, dan pembelajaran berbasis jaringan yang membantu meningkatkan partisipasi peserta didik, keleluasaan belajar, dan refleksi spiritual. Di sisi lain, penelitian ini juga menemukan beberapa tantangan, seperti rendahnya literasi digital guru, penggunaan teknologi yang masih berfokus pada aspek teknis, serta potensi pembelajaran spiritual yang bersifat dangkal. Kajian ini memberikan gambaran mengenai penerapan connectivism dalam Pendidikan Agama Kristen, khususnya yang berkaitan dengan pedagogi digital dan spiritual learning di era digital. Hasil penelitian diharapkan dapat menjadi bahan pertimbangan dalam pengembangan model pembelajaran Pendidikan Agama Kristen yang lebih sesuai dengan kebutuhan pembelajaran masa kini.